2013
DOI: 10.5301/hip.2013.11049
|View full text |Cite
|
Sign up to set email alerts
|

Cemented Total Hip Arthroplasty in Rheumatoid Arthritis. A Systematic Review of the Literature

Abstract: Considering the relatively frequent reports of increased infection rates in combination with the potential under-registration of complications, RA patients have to be considered to have a mild increased risk of postoperative infection. Case series and registries cannot answer the question of whether RA is a risk factor for dislocation as multivariate analysis is required. Increased rates of cup and stem failure due to aseptic loosening in RA patients are found in older but not in more recent studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Periprosthetic joint infection is one of the most dreaded complications after THA. The association between increased risks of infection in RA patients undergoing THA has been frequently studied [ 25 ]. There have been reports of increased risk of infection in patients with RA compared with patients with OA [ 26 ], possibly due to the systemic autoimmune disorder.…”
Section: Complications Of Tha In Patients With Ra and Causative Famentioning
confidence: 99%
“…Periprosthetic joint infection is one of the most dreaded complications after THA. The association between increased risks of infection in RA patients undergoing THA has been frequently studied [ 25 ]. There have been reports of increased risk of infection in patients with RA compared with patients with OA [ 26 ], possibly due to the systemic autoimmune disorder.…”
Section: Complications Of Tha In Patients With Ra and Causative Famentioning
confidence: 99%
“…Immunosuppressive agents can inhibit the proliferation and function of T and B lymphocytes related to immune response by affecting the body's immune response and immunopathological response, thereby reducing the immune response of antibody and increasing the body's susceptibility. Zwartelé and Pöll observed 292 patients with hip replacement who took long-term oral immunosuppressants in 36-year followup, and found that the incidence of PJI in users of immunosuppressive agents was significantly higher than that of non-users [18]. Hypoalbuminemia not only shows fiber proliferation and the lack of raw materials for collagen synthesis, delayed injury healing, decreased plasma colloid osmotic pressure, edema formed by osmotic retention of tissue, but also results in reduction of antibody synthetase, leading to decreased body immunity and increased chance of infection.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 But a systematic review of cemented total hip arthroplasty in rheumatoid arthritis showed increased rates of aseptic loosening among 10 out of 20 case series on the cup and six out of 19 in the stem. 14 Many comparative studies on cemented and uncemented implants finally concluded that the survival rate of cemented implants is better than uncemented implants and it is also better for osteoarthritis patients rather than rheumatoid arthritis patients. 15 Nevertheless, our study had not shown any of the complications which were encountered in other literature reviews either cemented or uncemented implants.…”
Section: Resultsmentioning
confidence: 99%